FUNGSI MONITORING KEPALA DINAS PADA PENERAPAN STANDAR PELAYANAN MINIMAL DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN MINAHASA UTARA (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract : A service standards needs to be monitored in its implementation, and the monitoringfunction can find quickly, so that a mechanism for resolving and setting up a mechanism for preventioncan be developed. Study aims to explain the monitoring function of the head department on the aplicationof minimum service standards in the department population and civil registration in north minahasa. Basedon the results and discussion of this research concluded, has not done well seen in the four functionsmonitoring is compliance, auditing, accounting, and explanation. Needed public awareness for orderlypopulation administration and leadership must be more active in monitoring the course of service and theseriousness of the goverment to create a strategy.This research uses qualitative research methods, descriptive. informant research by as much as 10(ten) informant: 1 person head of Department, 1 Secretary, 1 head of the sub. the General section and thestaffing, 5 civil State apparatus, 2 people community. data collection techniques used i.e., interviewtechniques, techniques of observation/observation, and technical documentation. data analysis techniquesused, namely the reduction of data, data presentation, and conclusion.Key words : Monitoring Function, Minimum Service Standards